Unconscious goal activation and the hijacking of the executive function. [article]. - Marien, Hans.
Building on research on unconscious human goal pursuit and the dynamic nature of our mental and physical world, this study examined the idea that an unconsciously activated goal hijacks executive control for its own attainment. This "hijacking" of the executive function by an unconscious goals should be evidenced by impaired performance on an unrelated task relying on executive control. The results of 6 experiments show that subliminal activation of a socializing goal, or an idiosyncratic personal goal, or an academic goal, harmed participants' performance on executive function task, such as inhibition of prepotent responses and detection of text errors during reading. These effects were unique to executive control, were similar when the goal was activated consciously, and were independent of task motivation and perceived inter-goal relatedness between the primed goal and task goal. Furthermore, an unconscious goal occupied executive control to advance itself more strongly when the goal had personal value. Implications for theory and research on unconscious goal pursuit and the executive function are discussed. -(from the author)
Keywords: Unconcious goal pursuit; Executive function; Subliminal priming